- (a+b)
^{2}= a^{2}+ b^{2}+ 2ab

or it can also be written as:

(a+b)^{2}= (a-b)^{2}+ 4ab - (a-b)
^{2}= a^{2}+ b^{2}- 2ab

or it can also be written as:

(a-b)^{2}= (a+b)^{2}- 4ab - (a+b)
^{3}= a^{3}+ b^{3}+ 3ab(a+b) = a^{3}+ b^{3}+ 3a^{2}b + 3ab^{2} - (a-b)
^{3}= a^{3}- b^{3}- 3ab(a-b) = a^{3}- b^{3}- 3a^{2}b + 3ab^{2} - a
^{3}+ b^{3}= (a+b)^{3}- 3ab(a+b)

or it can also be written as:

a^{3}+ b^{3}= (a+b) (a^{2}-ab+b^{2}) - a
^{3}- b^{3}= (a-b)^{3}+ 3ab(a-b)

or it can also be written as:

a^{3}- b^{3}= (a-b) (a^{2}+ab+b^{2}) - a
^{2}- b^{2}= (a-b)(a+b) - a
^{m}* a^{n}= a^{m+n} - a
^{m}/ a^{n}= a^{m-n} - (a/b)
^{(m/n)}= (b/a)^{-(m/n)} - a
^{m}/ b^{-n}= a^{m}* b^{n}

- x² – 34x + 288 = 0

y² – 28y + 192 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 26x + 168 = 0

y² – 32y + 252 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² + 26x + 168 = 0

y² + 23y + 132 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 44x + 448 = 0

y² – 28y + 195 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 26x + 168 = 0

y² – 34y + 285 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 38x + 352 = 0

y² – 25y + 154 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² = 121

y² – 46y + 529 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² + 29x + 208 = 0

y² + 19y + 78 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 41x + 400 = 0

y² – 29y + 210 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y - x² – 25x + 156 = 0

y² – 32y + 255 = 0

A. X > Y

B. X < Y

C. X ≥ Y

D. X ≤ Y

x² – 34x + 288 = 0

x = 18, 16

y² – 28y + 192 = 0

y = 12, 16

x² – 26x + 168 = 0

x = 12, 14

y² – 32y + 252 = 0

y = 14, 18

x² + 26x + 168 = 0

x = -12, -14

y² + 23y + 132 = 0

y = -12, -11

x² – 44x + 448 = 0

x = 28, 16

y² – 28y + 195 = 0

y = 13, 15

x² – 26x + 168 = 0

x = 12, 14

y² – 34y + 285 = 0

y = 15, 19

x² – 38x + 352 = 0

x = 22, 16

y² – 25y + 154 = 0

y = 11, 14

x² = 121

x = 11, – 11

y² – 46y + 529 = 0

y = 23, 23

x² + 29x + 208 = 0

x = -13, -16

y² + 19y + 78 = 0

y = -13, -6

x² – 41x + 400 = 0

x = 25, 16

y² – 29y + 210 = 0

y = 14, 15

x² – 25x + 156 = 0

x = 12, 13

y² – 32y + 255 = 0

y = 15, 17